Quantifying impacts of consumption based charge for carbon intensive materials on products - Stefan Pauliuk; Karsten Neuhoff; Anne Owen; Richard Wood (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
After the Paris Climate Agreement, it is anticipated that carbon prices will differ across regions for some time. If countries use free allowance allocation as carbon leakage protection, only a fraction of carbon prices are passed through to consumers particularly by carbon intensive materials producers. Adding a consumption charge based on benchmarks applied to the material content can reinstate the carbon price signal. The paper investigates the implications of such a consumption charge for industry and consumers based on material flow analysis and material flow cost accounting. The material-related carbon liabilities for production, import, export, and consumption are estimated for 4000 commodity groups that contain one or more of the five bulk materials steel, aluminium, plastics, paper, and cement. Assuming an underlying carbon price of 30 Euros per ton of CO2, the total charge to European final consumers is estimated to be about 17 billion EUR. The total charges levied on imports and those waived for exports are each of similar size and roughly amount to half of the total charge to European final consumers. To reduce administrative efforts, the charge is not levied on imported products for which the value of the consumption charge compared to product price falls below a threshold. Thus administrative efforts for 77 to 83% of imports could be avoided while still 85% to 90% of import-related carbon liabilities are included.
Keywords: F18; H23; Q56; 330; Material flow analysis; Material flow cost accounting; Carbon Pricing; Inclusion of Consumption; EU Emissions Trading System